The Effect Of Joint Offset Between The First And Second Axes On Kinematic Performance Of Anthropomorphic Robots - shneiaa, taymaa (Latakia University Journal -Engineering Sciences Series, 2025)
In this study, we examine a family of manipulators with six revolute joints, where the first joint axis is perpendicular to the subsequent parallel joint axes.This structure is the most widespread among industrial robots and is used in the basis of human-like robots called anthropomorphic. Although the kinematic characteristics of such robots are generally known in terms of the shape of the workspace and the presence of singular points, there remains a gap in knowing which one is the best with the variation of DH parameters. The members of this family are characterized by being non-specific and consequently none of them are cuspidal. Thus they does not have the ability to change their posture without passing through a singularity. This explains why there was almost no interest in classifying such family of robots in terms of their kinematic performance according to DH parameters, especially with the presence of other robots that are more attractive in terms of their stable dynamic performance such as parallel robot, and the existence of orthogonal robots of which families with distinctive features were found in terms of their kinematic properties. In this study, we are interested to select from the design parameters space the optimal DH parameters for the aforementioned family of robots that improves their kinematic properties, namely the offset between the first and the second joint axes. In the design optimization problem, several kinematic criteria were adopted separately, such as manipulability and dexterity. These robots were then divided into classes according to the shape of the worst region in the work space according to the values of one of the DH parameters.